Analisis Penggunaan Media Pembelajaran Quizizz terhadap Hasil Belajar Siswa SD Kota Palangka Raya - Putri Silvia; Kumala Azahra Majidiah; Wafiq Nabila; Jadiaman Parhusip (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to analyze the effect of implementing learning media through the Quizizz application on student learning outcomes in grade V. This study uses an experimental design by comparing two groups, namely the experimental class using Quizizz and the control class using conventional learning methods. The research instrument is a learning outcome test consisting of pretest and posttest questions. The results of the study indicate that the application of Quizizz can significantly improve student learning outcomes. Statistical tests conducted on pretest and posttest data show significant differences between the experimental class and the control class. The results of the validity and reliability of the instrument also show that the test used has good quality. Based on these findings, it can be concluded that the use of Quizizz as a learning medium can improve student learning outcomes and can be applied in the learning process to improve teaching effectiveness.